Assessing Factors Affecting Property Rate Compliance Behaviour in Ghana: The Case of Ga East Municipality - Samuel, G. (University Of Ghana, 2017)
Property taxation is the backbone of local government revenue across the globe. Thus, property tax non-compliance behaviour threatens the independence, sustainability and development effort of local governments. This study sought to examine factors affecting property rate compliance behaviour in Ghana: the case of Ga East Municipality. Specifically, the study sought to assess property owners‟ level of knowledge of property rate laws, and the determinant factors of compliance behaviour. The study employed a mixed method. A total of 120 property owners were interviewed using a survey instrument and two key informant interviews were conducted with the Municipal Rating Office and the Municipal Deputy Finance Director. Logistic regression model was used to examine determinants of property rate compliance behaviour while descriptive statistics was used to asses knowledge of property rate law among property owners. Findings of the study indicate that majority of the property owners representing 53 per cent are not aware of property rate laws in Ghana. Logistics regression result also shows that female property owners are more likely to pay property rate then male property owners. Also, property owners perception of the complexity of the tax system was found to significant negatively correlated with rate compliance behaviour. However, knowledge of property rate laws and rate education was found to have no significant relationship with rate compliance. The study therefore recommends that property rate education focus on providing owners with education that helps them to understand the tax system, and the adoption of compliance process that eliminate human interaction and facilitate easy compliance with respect to time and cost.
Thesis (M.A.)
Keywords: Property Rate; Property Taxation; Government Revenue; Compliance; Ghana